2008
DOI: 10.1007/s00606-008-0015-1
|View full text |Cite
|
Sign up to set email alerts
|

The systematic value of nuclear DNA content for all species of Narcissus L. (Amaryllidaceae)

Abstract: The taxonomy of all species of Narcissus (Amaryllidaceae), an important horticultural crop, has not been investigated recently. As a new approach, genome size was determined by flow cytometry with propidium iodide from 375 accessions. The somatic nuclear DNA contents (2C) were shown to range from 14 to 38 pg for the diploids. Narcissus assoanus and N. gaditanus are, based on their nuclear DNA content, removed from section Apodanthi and placed in a new section Juncifolii. The different ploidy levels and species… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
75
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(82 citation statements)
references
References 34 publications
6
75
0
1
Order By: Relevance
“…These were compared with the genome sizes of all species (Zonneveld, 2008, Table 1). It turns out that doubling of the nuclear DNA content of 23.8 pg of N. pseudonarcissus falls short of the values found for the trumpet daffodils (Table 3).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…These were compared with the genome sizes of all species (Zonneveld, 2008, Table 1). It turns out that doubling of the nuclear DNA content of 23.8 pg of N. pseudonarcissus falls short of the values found for the trumpet daffodils (Table 3).…”
Section: Resultsmentioning
confidence: 99%
“…Morphological similar looking species of trumpet daffodils of section Pseudonarcissi with a com plementing higher amount of nuclear DNA like N. hispanicus with 25.8 pg, N. poeticus with 26 pg and the hexaploid N. pseudonarcissus ssp. bicolor with 67.7 pg (Zonneveld, 2008) were selected and data on Table 2. Narcissus cultivars with their amount of nuclear DNA, average, standard deviation, chromosome number, origin and remarks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Primitive angiosperms are now supposed to have had small genomes; increases up to a factor of 1,000 have occurred independently in various modern taxa (Leitch et al 1998). Flow cytometry was successfully used to measure the 2C-value for the genera Hosta Tratt., Helleborus L., Clivia Lindl., Nerine Herb., Agapanthus L'Hér., Galanthus L., Narcissus L., Gasteria Duval., Tulipa L., etc., by Zonneveld ( , 2008Zonneveld ( , 2009), Zonneveld and Van Iren (2001), Duncan (2003, 2006), Zonneveld and Van Jaarsveld (2005) and . In this paper it is shown that genome size alone is not sufficient to discriminate all species of Eucomis.…”
Section: Introductionmentioning
confidence: 98%